ESTIMATION OF CARBON STORAGE IN SHRUBS IN CEMPAKA SUBDISTRICT, BANJARBARU - Rahmani, Dienny Redha; Wahyunah, Wahyunah; Louisa, Virgina Maria (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2016)
The amount of critical lands, mostly wetlands, in South Kalimantan Province has increased, and it requires quick and sustainable recovery. An analysis of the potential of shrubs in vegetation indicated that shrubs had an important role in greening a city either in mixed vegetation or in vegetation filled with shrub strata. This basic characteristic becomes the basis of the study on carbon storage in shrubs and their potential as the alternative vegetation in the recovery of degraded lands. The study was conducted in Cempaka Subdistrict, Banjarbaru. Samples were taken at three stations, each of which consisted of three plots sample plots measuring 4 x 4 m. Carbon storage in the shrubs was estimated using the main stem diameter, and converted into table of average carbon estimation. The shrub canopy was estimated based on the types of canopy using formulas and types of canopy volume. The results showed that the average value of carbon storage contained in the shrubs per plot was 15.54 lbs/m2/day, with an average canopy volume per plot was 0.40 m3. In 1 ha of growing area, shrubs was estimated to absorb carbon up to 155,416.67 lbs. Total canopy volume developed by the shrub vegetation in the area was 22,462,878.50 m3/ha. The canopy volume has a correlation with carbon storage in shrubs, so shrubs are potential as the initial alternative vegetation or pioneer plants for reforestation of degraded land.